2020
DOI: 10.1051/e3sconf/202022202030
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of parental material of winter rapeseed (Brassica napusL.) and winter brown mustard (Brassica junceaL.) on resistance to Phoma rot in the central zone of the Krasnodar region of the Russian Federation

Abstract: In 2018-2020, Phoma rot (Leptosphaeria maculans Ces. & De Not) in the form of stem canker was the most common disease on winter rapeseed and winter brown mustard in the central zone of the Krasnodar region of the Russian Federation. Given the high prevalence and development of the disease in all years of research, we identified the rapeseed samples resistant to it; they had the affection degree of 1-2 points (9.0-12.0% of the total number of studied samples). The rest of the samples were weakly resistant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…The analysis of the data in Table 1.27 confirms that the resistance of the spring rape variety Kalinovsky is manifested in the ability of affected plant cells to induce an increase in the amount of peroxidase. In addition, our studies also revealed [445] an increase in lignin biosynthesis in the affected tissues of spring rape.…”
Section: Prevalence and Damage Of Major Diseases Of Cruciferous Cropssupporting
confidence: 69%
See 3 more Smart Citations
“…The analysis of the data in Table 1.27 confirms that the resistance of the spring rape variety Kalinovsky is manifested in the ability of affected plant cells to induce an increase in the amount of peroxidase. In addition, our studies also revealed [445] an increase in lignin biosynthesis in the affected tissues of spring rape.…”
Section: Prevalence and Damage Of Major Diseases Of Cruciferous Cropssupporting
confidence: 69%
“…It has also been proven [445], that in the resistant variety Kalinovsky, the difference in ascorbic acid content in healthy and downy mildew-affected leaves was 2.7 mg%, and in phomosis -3.4 mg%. At the same time, in the relatively susceptible variety Valero, the difference was 12.6 mg% in the first case and 13.9 mg% in the second (Table 1 Similar studies have also shown the role of ascorbic acid in the identification of spring rape downy mildew.…”
Section: Prevalence and Damage Of Major Diseases Of Cruciferous Cropsmentioning
confidence: 94%
See 2 more Smart Citations
“…The stem tissues in this area as well as above and below the necroses become rotted, the stem breaks at this point and the plant becomes lodged. And even if the seeds are formed, they will fall out of the pods or rot inside them [7,8].…”
Section: Introductionmentioning
confidence: 99%